HUBUNGAN RASA HUMOR DAN INTELIGENSI DENGAN KREATIVITAS VERBAL SISWA SMP NEGERI DI KOTA MEDAN - Aida Fitriany; Abdul Munir (Analitika: Jurnal Magister Psikologi UMA, 2010)
Basicallythis study aims to look at the relationship between sense of humor and intelligence with verbal creativity in junior high school students in the city of Medan.The results obtained are as follows. There is a positive relationship between sense of humor and intelligence with verbal creativity. These results indicated by coefficients which Freg = 28.424 p <0.010. This indicates that the higher the higher the sense of humor and intelligence, it is also higher verbal creativity. Conversely the lower the lower the sense of humor and intelligence, it is also the lower the verbal creativity. 2). There is a significant positive relationship between sense of humor with verbal creativity by controlling the variables of intelligence. It is seen from the coefficient of correlation = 0.174, p <0.050. Based on these results the hypothesis been accepted. Then note that a sense of humor contributed to the verbal creativity of only 1.407%. 3). There is a very significant positive relationship between intelligence with verbal creativity by controlling the variable sense of humor. It is seen from the coefficient of correlation = 0.458, p <0.010. Based on these results the hypothesis been accepted. Then known that intelligence contributes to the verbal creativity of 20.187%.